2021
DOI: 10.1016/s2214-109x(21)00228-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a multifaceted intervention to improve clinical quality of care through stepwise certification (SafeCare) in health-care facilities in Tanzania: a cluster-randomised controlled trial

Abstract: Background Quality of care is consistently shown to be inadequate in health-care settings in many low-income and middle-income countries, including in private facilities, which are rapidly growing in number but often do not have effective quality stewardship mechanisms. The SafeCare programme aims to address this gap in quality of care, using a standards-based approach adapted to low-resource settings, involving assessments, mentoring, training, and access to loans, to improve clinical quality and facility bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Eleven studies evaluated the impacts of various forms of regulation of health facilities on QoC 232–242. In South Africa, hospital accreditation was associated with improved compliance with quality standards.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven studies evaluated the impacts of various forms of regulation of health facilities on QoC 232–242. In South Africa, hospital accreditation was associated with improved compliance with quality standards.…”
Section: Resultsmentioning
confidence: 99%
“…The accreditation of health service providers linked to insurance payments in the Philippines improved quality scores among physicians in both public and private hospitals 238. Studies based on quality certification programmes were found in Egypt,236 India232 and Tanzania 237. In Ethiopia, clinical and administrative standards implementation improved quality in all areas assessed 234.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations